Clinical utility of neurofilament light chain as a biomarker for disease onset and progression in hereditary transthyretin amyloidosis - Gragera-Martínez, Álvaro; Borrachero Garro, Cristina; Muñoz Beamud, Francisco; Manovel Sánchez, Ana; González Macías, Andrés; Pizarro Sánchez, Mariano; Jiménez Heffernan, Amelia; Serrano Mira, Ana; Macías Dominguez, Beatriz; Garcia Garrido, Sandra (Frontiers in Neurology, 2025)
BackgroundNeurofilament light chain levels (NfL) have emerged as a biomarker for early diagnosis and follow-up of hereditary transthyretin variant amyloidosis (ATTRv). We evaluated the most accurate technique for NfL quantifying in ATTRv healthy carriers and symptomatic patients in real-life practice, and assessed whether NfL may represent a reliable biomarker of disease onset and progression.MethodsSerum NfL were measured using ELISA and the single-molecule array (SIMoA) technique. Disease severity was assessed with a polyneuropathy disability score (PND).ResultsSeventy-five subjects with pathogenic transthyretin variant (40 ATTRv healthy carriers and 35 ATTRv patients) were enrolled. We observed a significant correlation between ELISA and SIMoA assay (Pearson’s R2-value = 0.9899). Compared to healthy carriers, patients with symptomatic ATTRv had statistically higher serum NfL levels (p < 0.001). We propose a NfL cut-off of 7.9 pg./mL to distinguish between healthy carriers and ATTRv patients with high diagnostic accuracy (AUC = 0.847; p < 0.001; sensitivity = 90.0%; specificity = 55.0%), whereas the NfL threshold of 18.4 pg./mL discriminated the transition from patients with PND I to PND ≥ II (AUC = 0.695; p < 0.001; sensitivity = 67.0%, specificity = 86%).ConclusionSerum NfL can be accurately quantified using both ELISA and SIMoA array, and it seems to be a reliable biomarker to detect the transition from presymptomatic to symptomatic disease onset and to monitor disease progression.